Regulation of glutamine synthetase activity by transcriptional and posttranslational modifications negatively influences ganoderic acid biosynthesis in Ganoderma lucidum. (26th January 2021) - Zhu, Jing; Song, Shuqi; Sun, Zehua; Lian, Lingdan; Shi, Liang; Ren, Ang; Zhao, Mingwen
Summary: Glutamine synthetase (GS), a central nitrogen metabolic enzyme, plays important roles in the nitrogen regulation network and secondary metabolism in fungi. However, the mechanisms by which external nitrogen sources regulate fungal GS activity have not been determined. Here, we found that GS activity was inhibited under nitrate conditions in Ganoderma lucidum . By constructing gs ‐silenced strains and adding 1 mM GS inhibitor to inhibit GS activity, we found that a decrease in GS activity led to a decrease in ganoderic acid biosynthesis. The transcription of gs increased approximately five fold under nitrate conditions compared with that under ammonia. Electrophoretic mobility shift and yeast one‐hybrid assay showed that gs was transcriptionally regulated by AreA. Although both gs expression and GS protein content increased under nitrate conditions, the GS activity still decreased. Treatment of recombinant GS with SIN‐1 (protein nitration donor) resulted in a strengthened nitration accompanied by a 71% decrease in recombinant GS activity. Furthermore, intracellular GS could be nitrated from mycelia cultivated under nitrate conditions. These results indicated that GS activity could be inhibited by NO‐mediated protein nitration. Our findings provide the first insight into the role of transcriptional and posttranslational regulation of GS activity in regulating secondary metabolism in fungi.